Visualization of Road Access Using GIS Based on GNSS Observation at Taman Universiti Parit Raja, Batu Pahat - Hajar, Siti (Recent Trends in Civil Engineering and Built Environment, 2021)
Geographic Information System (GIS) is a system of hardware, software and procedures to facilitate the management, manipulation, analysis, modelling, representation and display of geo-referenced data to solve complex problem regarding planning and management of resources. This study will conduct to give knowledge to people and to identify the physical features of the study area such as morphology of the selected route and topography of the area by using QGIS software. The data that can obtain from this software is combination of raster data, vector data and attributes data so from the data the public or authorities can use it freely to develop that area. Authorities and developer also use GIS software to analyses the characteristics of data in any area for development purpose before starting the project. This will help consultant and contractors that involved in the project aware to the situation in map. Application of QGIS can be in order to find the accurate topography and morphology data for the selected area. The use of Google Earth Pro have certain deficiency where the image of the area will not clearly been observed.